Metal Hypersensitivity in Total Joint Arthroplasty. Issue 12 (December 2018) - Eftekhary, Nima; Shepard, Nicholas; Wiznia, Daniel; Iorio, Richard; Long, William John; Vigdorchik, Jonathan
Abstract : Metal hypersensitivity has been reported in various case reports and cohort studies. Type-IV (delayed-type) hypersensitivity to various implant metals, most frequently nickel, has been implicated in the pathogenesis of metal hypersensitivity. Currently, there are no guidelines for addressing suspected or known metal allergy preoperatively and there is no evidence-based support for either preoperative testing or routine use of hypoallergenic implants. Multiple diagnostic modalities are available for the workup of suspected metal hypersensitivity; the 2 most common are patch testing and lymphocyte transformation testing. However, the ability of these tests to diagnose disease and predict outcomes has not yet been demonstrated. Further research is warranted to help understand the prevalence, pathology, diagnosis, treatment, and potential avoidance of metal hypersensitivity.